Variabilidade da frequência cardíaca nos domínios do tempo, frequência e caos em recém-nascidos prematuros pré-extubação - Silva, Marciali Gonçalves Fonseca (2011)
The prematurity with their comorbidities can result in a long period of mechanical ventilation in the intensive care unit. A method for the diagnostic assessment of organic maturity would be useful for this population. The heart rate variability (HRV), as an indicator of homeostasis, presents this profile. Objective: The purpose of this research was to assess the HRV in neonates intubated in the neonatal intensive care unit (ICU) of Hospital de Base before extubation. Casuistic and Method: A total of 44 neonates, 16(36.4%) males and 28(63.6%) females, in neonatal ICU at Hospital de Base (HB) of São José do Rio Preto were prospectively studied. HRV was evaluated in time, frequency and chaos by recording of electrocardiographic times series with the aid of a Polar RS800. The results obtained in this study group (RNP2) were compared with samples previously studied of preterm neonates of neonatal ICU of Curitiba (RNP1) and term neonates of HB (RNT). Results: There was no significant difference among clinical findings of neonates with and without of extubation failure. The results of 47 records of HRV revealed in time a significant difference among the groups RNT x RNP1 for mean RR intervals (MeanRR) (p < 0.0001), RMSSD (p < 0.0001), and PNN50 (p = 0.0012); SD1 e SD2 (p < 0,0001) and SD1/SD2 rate (p = 0,0448); RNT x RNP2 for MeanRR (p < 0.0001) and RMSSD (p = 0.0034); SD1 (p = 0,0036) e SD2 (p = 0,0002) among RNP1 x RNP2 for MeanRR (p = 0.0016) and SD1/SD2 rate (p = 0,0443). In the frequency, significant differences were found among RNT x RNP1 for LF ms2, HF ms2, total ms2 (p < 0.0001 in all these measurements), LF/HF ratio (p = 0.0031); RNT x RNP2 for LF ms2 (p < 0.0001), HF ms2 (p = 0.0048), total ms2 (p < 0.0001), and among RNP1 x RNP2 for LF/HF ratio (p < 0.0017). In chaos, there was significant difference among RNT x RNP1 for mean line length (Lmean), recurrence rate (RecRate), Shannon's entropy (p < 0.0001 in all these measurements), and determinism rate (DET) (p = 0.004); RNP1 x RNP2 the difference was significant for Lmean (p = 0.0188), RecRate (p = 0.029), DET (p = 0.0472), and Shannon's entropy (p = 0.0205). Conclusions: In time, frequency, and chaos, HRV was not considered as predictive value to extubation failure, but in intubated neonates this methodology present potential of clinical application. Neonates with good clinical conditions and greater development of autonomic nervous system show largest HRV, mainly in the chaos domain, indicating greater homeostatic balance similar to the pattern of term neonates.